Factores de riesgo y su relación con la bronquitis crónica en adultos mayores de la ciudadela 4 de mayo, Babahoyo Los Ríos, periodo septiembre 2017 a febrero 2018 - Romero Chica, Jose Joel (2018)
The chronic bronchitis is an inflammation of the bronchial conduits which transport the oxygen towards the lungs, this is a long-term illness that once contracted never disappears completely and has no cure. The most common symptoms that this illness presents are: persistent cough with abundant expectoration, shortness of breath and pain top sideways. This type of bronchitis occupies the third place because of death on a global scale and in our country it is considered to be one of the illnesses that it attacks often the major adults that, therefore, for our investigation we determine the factors of risk of this illness to which the biggest adults of the ciudadela 4 de mayo, in order to discover the way of reducing the high numbers of morbimortality of this illness.